A Comparison of The Effects of Clobetasol 0.05% and Photodynamic Therapy Using Aminolevulinic Acid With Red Light in the Treatment of Severe Nail Psoriasis - Tehranchinia, Zohreh; Barzkar, Nasibeh; Riahi, Seyed Mohammad; Khazan, Marjan (Journal of Lasers in Medical Sciences, 2020)
Introduction: The treatment of nail psoriasis is often difficult and unsatisfactory due to therapy resistance. This study aimed to compare the efficacy of clobetasol 0.05% ointment and photodynamic therapy (PDT) using aminolevulinic acid (ALA) and red light in the treatment of severe nail psoriasis. Methods: This open-trial study included 69 nails of 8 patients with severe nail psoriasis. Thirty-four nails were treated with clobetasol 0.05% ointment and 35 nails were treated with ALA-PDT. ALA-PDT treatment was performed every 3 weeks for 5 cycles; the nails were treated with clobetasol under occlusion every day during the study. All the patients were followed up after 24 weeks. The severity of nail involvement was measured by the Nail Psoriasis Severity Index (NAPSI) scores at the baseline and during the treatment. Results: There were no significant differences in the NAPSI scores between the treatment groups in the baseline and weeks 3, 6 and 9 (all P > 0.05), although significant differences were found in weeks 12, 15 and 24 (follow-up) (P < 0.001). A significant time-effect improvement was found in all the nail-matrix, nail-bed and total NAPSI scores in both treatment groups (all P < 0.001). The patients did not report intense pain and discomfort during irradiation. Conclusion: Clobetasol 0.05% ointment seems to be effective in treating nail psoriasis after a treatment period of 15 weeks. However, the efficacy of ALA-PDT at a 24-week follow-up was greater than that of clobetasol.